PERBANDINGAN PANDANGAN TOKOH UTAMA TERHADAP PROFESI PELACUR DALAM NOVEL PEREMPUAN DI TITIK NOL DAN NOVEL TUHAN, IZINKAN AKU MENJADI PELACUR! - Rokhmansyah, Alfian (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2016)
This study was focused on the comparison of view of life between the main character in the novel Perempuan di Titik Nol by Nawal el-Saadawi and the novel Tuhan, Izinkan Aku Menjadi Pelacur! by Muhidin M. Dahlan. As the method of analysis, content analysis was used along with objective approach. The results showed that there are similar views towards prostitute as profession from the two main female characters in both novel. The main character in the novel Perempuan di Titik Nol considers prostitute as her escape since she rejected to be the object to satisfy the lust of men without certain price. While the main character in the novel Tuhan, Izinkan Aku Menjadi Pelacur! considers prostitute as a force to restore her self-confidence in life.Keywords: comparison of novels, women’s points of view, main character, prostitute